2019
DOI: 10.29008/etc2019-311
|View full text |Cite
|
Sign up to set email alerts
|

A semi-empirical model for predicting the frequency of profile vortex shedding relevant to low-speed axial fan blade sections

Abstract: This paper extends existing semi-empirical models on the frequency prediction of vortex shedding. Moderate Reynolds numbers are investigated being of interest in low-speed axial fan design. By an extensive literature review, a new parametrization is proposed for the factor establishing a connection between boundary layer properties and vortex shedding characteristics. Measurement data on symmetrical and non-symmetrical NACA profiles, and on flat and cambered plates, are processed. It is found that the value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 18 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…b) Relative roughness (Ψ3 = k/c). As will be demonstrated later, the coefficient CD plays a substantial role in the semi-empirical model for PVS frequency prediction [32,37]. The effect of relative roughness is discussed herein via its influence on CD.…”
Section: ) Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…b) Relative roughness (Ψ3 = k/c). As will be demonstrated later, the coefficient CD plays a substantial role in the semi-empirical model for PVS frequency prediction [32,37]. The effect of relative roughness is discussed herein via its influence on CD.…”
Section: ) Results and Discussionmentioning
confidence: 99%
“…As demonstrated in Eq. ( 14), and emphasized already in the Introduction, the benefit of such Strouhal number is that, according to the measurement experiences [14][15]32], it can be regarded as constant.…”
Section: ) Semi-empirical Model For Predicting the Pvs Frequencymentioning
confidence: 94%
See 2 more Smart Citations
“…In [17] a NACA 0018 airfoil was investigated, and the results showed that, below Re C = 70000 (when the separated LBL fails to reattach) the f VS (Re C ) curve has 10 times lower slope, than in case Re C = 100000. Based on the above, the LBL VS is a complicated phenomenon, however, in the literature some semi-empirical formulas [6,18,19] can be found to predict the frequency of the LBL VS, which formulas are useful in the preliminary design of axial flow fans.…”
Section: Introduction and Objectivesmentioning
confidence: 99%